Snailfishes of the Careproctus rastrinus complex (Liparidae): redescriptions of seven species in the North Pacific Ocean region, with the description of a new species from the Beaufort Sea - Orr, James Wilder; Kai, Yoshiaki; Nakabo, Tetsuji (Zootaxa, 2015)
Herein we review and recognize as valid all previously described species of the Careproctus rastrinus complex based on morphological evidence, provide diagnoses and descriptions of all species, describe a new species from the Beaufort Sea, and address the misapplication of several names throughout the area. In particular, the name C. rastrinus is restricted to populations of the western Pacific and is known conclusively only from the Sea of Okhotsk. Careproctus acanthodes, from the Sea of Japan and Sea of Okhotsk, and C. pellucidus, from the Pacific Ocean side of northern Japan, are resurrected from synonymy with C. rastrinus. Populations of the eastern Pacific previously routinely identified as C. rastrinus are recognized under two names: C. scottae, a name that is applied to deeper water Bering Sea, Aleutian Islands, and eastern Pacific populations having a postorbital pore, and Careproctus phasma, applied to shallow water populations of the Bering Sea and Gulf of Alaska lacking a postorbital pore. Although we consider Careproctus spectrum valid, the species has been routinely misidentified and is presently known only from the type series. Careproctus lerikimae is a new species described from the Beaufort Sea, diagnosed from other species of the C. rastrinus complex by the absence of the postorbital pore and higher median fin and vertebral counts.